A phenomenological explication of the artistic creative experience of a painter, a writer and a playwright - Lambie, Eileen (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
The aim of the thesis was to explore two focus questions using the phenomenological approach. Firstly, what it meant to be an artist for three particular artists; a painter, a writer and a playwright. Secondly, what a general explicitation (after Van Kaam, 1958) of the three subjects' artistic creative experience and working processes revealed in essence. The taped data of the three artists were reduced and explored through a number of phenomenological strategies. This led to the formulation of four essential descriptions for each artist, which were based structurally on Van den Berg's experiential categories in A Different Existence. Thus, the essential descriptions reflect each artist's relationship with his/her world, body, fellow people and time. The final step was the achievement of a general extended description. The major conclusion arising from the phenomenological explication is that art affords a way through which artists are able to live an authentic existence. That is, the body and world of the artist are in harmony and the artist's art roots him in the past, is manifest in the present and indicates the future direction of his work. Another conclusion is that the artist is Janus-faced and this enables him/her to balance subjectivity and objectivity in the Lebenswelt and to communicate what he/she sees to others in a healthy way through art. The artist's relationship with world, body, fellow people and with time, is postulated as being qualitatively richer than that of the nonartist. The two focus questions were successfully answered through the research explication and were validated by two independent judges. The viability of the phenomenological approach in the field of artistic creativity was therefore demonstrated. Suggestions for future research were made, one of which was that more phenomenological research aimed at eliciting specific information on the creation of art works might render more information on the artistic creative process.
Keywords: Phenomenology; Art -- Philosophy; Artists; Creation (Literary, artistic, etc.)